2020
DOI: 10.1515/noise-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

A note on the acoustic environment in a usually quiet residential area after the ‘state of emergency’ declaration due to COVID-19 pandemic in Japan was lifted: supplementary survey results in post-emergency situations

Abstract: In a preceding report (UCL Open: Environment, 2020;1;6), an example of results on changes in the acoustic environment from a local-scale survey in a quiet residential area during and after the ‘state of emergency’ due to COVID-19 pandemic in Japan is presented: the noise level was 1–2 dBA lower during the state of emergency, which is smaller than reported from large cities. This note presents the results of a follow-up survey in the same area to provide some more examples to gain an insight into the acoustic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Thus, the changes in COVID-19 sound levels emerging from traffic borne-noise seem to be dependent on the local context, such as the strength of the lockdown and the comparative use of roads. Sound level reductions in cities that had overall fewer COVID-19-related restrictions had, in turn, smaller reductions in overall sound levels, such as Stockholm and Kobe, Japan [7,15].…”
Section: Reduction In Traffic Noisementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the changes in COVID-19 sound levels emerging from traffic borne-noise seem to be dependent on the local context, such as the strength of the lockdown and the comparative use of roads. Sound level reductions in cities that had overall fewer COVID-19-related restrictions had, in turn, smaller reductions in overall sound levels, such as Stockholm and Kobe, Japan [7,15].…”
Section: Reduction In Traffic Noisementioning
confidence: 99%
“…The study highlighted a park (Casa de Campo: adjacent to a zoo and amusement park) and showed that while levels were normally higher on weekend afternoons and evenings, the long plateau from those periods disappeared during their lockdown [20]. A study using six measurement points in Kobe (where there was a less strict State of Emergency in place, rather than a lockdown) showed a difference between weekdays and weekends, with weekday mornings being louder [15].…”
Section: Temporal Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the noise [8] associated with regular activities outdoors became almost nonexistent. Noise from traffic [9][10][11][12], railway noise, port noise [13], airport noise [14] and leisure-related noise [15] were substantially reduced in most of the analyzed cities [16][17][18], and even in quiet residential areas [19]. Nevertheless, everything seems to come back to normal after the harder episodes of the pandemic, and most of the cities around Europe have come back to their original noise levels in the street [20], maybe losing the opportunity to improve the noise impact on people.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the noise [8] associated with regular activities outdoors became almost nonexistent. Noise ground transportation, as traffic noise [9][10][11][12], railway noise, but also port noise [13], airport noise [14], industry noise [15] and leisure-related noise [16] were clearly reduced in the analyzed cities [17][18][19], and even in quiet residential areas [20].…”
Section: Introductionmentioning
confidence: 99%